2019
DOI: 10.1073/pnas.1912108116
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ablation of acid ceramidase in Krabbe disease confirms the psychosine hypothesis and identifies a new therapeutic target

Abstract: Infantile globoid cell leukodystrophy (GLD, Krabbe disease) is a fatal demyelinating disorder caused by a deficiency in the lysosomal enzyme galactosylceramidase (GALC). GALC deficiency leads to the accumulation of the cytotoxic glycolipid, galactosylsphingosine (psychosine). Complementary evidence suggested that psychosine is synthesized via an anabolic pathway. Here, we show instead that psychosine is generated catabolically through the deacylation of galactosylceramide by acid ceramidase (ACDase). This reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
98
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 30 publications
1
98
0
Order By: Relevance
“…The next step in the breakdown pathway is release of the fatty acyl group from ceramide by acid ceramidase (Figure 1). Recent studies have suggested that when GALC is deficient, acid ceramidase removes the fatty acyl chain from galactosylceramide to 2 of 7 generate psychosine ( Figure 1) [4]. Psychosine is thought to be a key cytotoxic agent that is responsible for loss of oligodendrocytes and Schwann cells that is the hallmark of Krabbe disease [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The next step in the breakdown pathway is release of the fatty acyl group from ceramide by acid ceramidase (Figure 1). Recent studies have suggested that when GALC is deficient, acid ceramidase removes the fatty acyl chain from galactosylceramide to 2 of 7 generate psychosine ( Figure 1) [4]. Psychosine is thought to be a key cytotoxic agent that is responsible for loss of oligodendrocytes and Schwann cells that is the hallmark of Krabbe disease [4].…”
Section: Introductionmentioning
confidence: 99%
“…Galactocerebrosidase (GALC)-catalyzed reaction and direct conversion of galactosylceramide to psychosine when GALC is deficient as proposed[4].…”
mentioning
confidence: 99%
“…In support of this hypothesis, in vitro studies show that treating cells with psychosine increases proapoptotic factors and kills oligodendrocytes (OL) 5 , Schwann cells 6,7 and neurons 8 . The long-held psychosine hypothesis was recently confirmed, in vivo, which demonstrated that the abnormal accumulation of psychosine is toxic and is generated catabolically through the deacylation of galactosylceramide by acid ceramidase 9 More than 85% of KD patients exhibit the rapidly progressive infantile-onset form of disease, which leads to death by two years of age. Although there is no cure for Krabbe disease, hematopoietic stem cell therapy (HSCT) attenuates neurologic deterioration and improves developmental gains 10 .…”
Section: Introductionmentioning
confidence: 94%
“…3. Krabbe disease (OMIM #245200) is caused by a deficiency of GALC (Galactosylceramidase), which leads to the accumulation of psychosine (galactosylsphingosine), a metabolite of galactosylceramide (Li et al, 2019). Clinical symptoms often present in the 1st year of life including irritability, spasticity and developmental delay.…”
Section: Metachromatic Leukodystrophy (Mld Omim #250100)mentioning
confidence: 99%
“…Clinical symptoms often present in the 1st year of life including irritability, spasticity and developmental delay. Underlying pathology includes widespread demyelination and neurodegeneration (Li et al, 2019). HSCT appears to be of some benefit in cases of later onset or in infantile patients who have been diagnosed before symptoms begin (Wright et al, 2017).…”
Section: Metachromatic Leukodystrophy (Mld Omim #250100)mentioning
confidence: 99%